2018
DOI: 10.1155/2018/8298527
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity of Working-Age People in View of Their Income Status

Abstract: Objective The study examines relationships between physical activity levels and income status of working-age city residents. Methods The study was carried out in the years 2014 and 2015 in Wrocław, Poland. The study sample comprised 4332 participants (2276 women; 2056 men) aged 18 to 64 years. Respondents' habitual physical activity levels were measured with the International Physical Activity Questionnaire Short Form (IPAQ-SF), while their income status was assessed with author's own Socio-Economic Status of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…Second, the leisure-time PA is higher among those who have high income than those with a low income. The individuals with a low income use part of their free time for extra-paid work that can be otherwise utilized for undertaking free-time PA. 47 This study shows a "lack of time" (OR = 4.480; CI, 1.660-12.090; P = .003) as the only barrier that significantly influenced the PAL. This finding was also supported by a study that reported "lack of time"…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Second, the leisure-time PA is higher among those who have high income than those with a low income. The individuals with a low income use part of their free time for extra-paid work that can be otherwise utilized for undertaking free-time PA. 47 This study shows a "lack of time" (OR = 4.480; CI, 1.660-12.090; P = .003) as the only barrier that significantly influenced the PAL. This finding was also supported by a study that reported "lack of time"…”
Section: Discussionmentioning
confidence: 68%
“…45 Current study identified higher income as a predictor of high level of PA that is supported by other studies. 47,48 This finding can be interpreted in a twofold way. 47 First, it can be explained by the substantial contribution of PA related to the performance of professional tasks and of commuting to one's total physical effort.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A nationally representative survey from Korea showed that adolescents with a low level of household income, whose fathers had a low level of education, were more likely to have an early initiation into smoking and drinking alcohol [31]. A study carried out in Poland in a working-age population found that respondents with a steady and higher income had the highest physical activity levels [32]. A cross-sectional analysis conducted in Germany with nearly 20,000 adults demonstrated that multimorbidity, defined as the presence of more than one chronic disease at the same time in one individual, was associated with the age and education of participants [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, in none of them, special devices for PA in IVR were used. Meanwhile, the percentage of population with PA recommended for health by international organizations is low regardless of age or socioeconomic status [54,55,56]. AVGs in IVR helps to eliminate periods of lack of PA, characteristic to traditional computer games, which are one of the most popular leisure-time activities.…”
Section: Discussionmentioning
confidence: 99%